CellGAN: Generative Adversarial Networks for Cellular Microscopy Image Recognition with Integrated Feature Completion Mechanism - Xiangle Liao; Wenlong Yi (Applied Sciences, 2024)
In response to the challenges of high noise, high adhesion, and a low signal-to-noise ratio in microscopic cell images, as well as the difficulty of existing deep learning models such as UNet, ResUNet, and SwinUNet in segmenting images with clear boundaries and high-resolution, this study proposes a CellGAN semantic segmentation method based on a generative adversarial network with a Feature Completion Mechanism. This method incorporates a Transformer to supplement long-range semantic information. In the self-attention module of the Transformer generator, bilinear interpolation for feature completion is introduced, reducing the computational complexity of self-attention to O(n). Additionally, two-dimensional relative positional encoding is employed in the self-attention mechanism to supplement positional information and facilitate position recovery. Experimental results demonstrate that this method outperforms ResUNet and SwinUNet in segmentation performance on rice leaf cell, MuNuSeg, and Nucleus datasets, achieving up to 23.45% and 19.90% improvements in the Intersection over Union and Similarity metrics, respectively. This method provides an automated and efficient analytical tool for cell biology, enabling more accurate segmentation of cell images, and contributing to a deeper understanding of cellular structure and function.